Strategi Guru dalam Menerapkan Pembelajaran Individual bagi Siswa Berkebutuhan Khusus Tingkat SMA: Studi Kasus di Sekolah Khusus Bina Ihsan Mandiri - Maryam; Akhmad Riadi; Latifah Nur Aprilyani; M. Habil Al-Faqih; Asaranum Sila Safitri; Humaida; Lina Oktaviani (CV. Ulil Albab Corp, 2026)
The implementation of Individualized Education Programs (IEP) for students with special needs at the senior high school level often faces challenges in adjusting complex academic materials. This research aims to analyze teacher strategies in the planning, implementation, and evaluation of individualized learning for students with autism, intellectual disabilities, and deafness at Bina Ihsan Mandiri Special High School. Using a qualitative case study approach, data were collected through observation, semi-structured interviews, and documentation. Research results indicate that teachers implement adaptive strategies through material modification into concrete forms for students with intellectual disabilities, the utilization of visual media for deaf students, and structured instructions for students with autism. Time flexibility and persuasive approaches are consistently used to maintain student focus and engagement. Assessments are conducted continuously by adjusting to the individual capacity of each student. Although instructional strategies are effective, the primary obstacle found is the low level of synergistic collaboration between the school and parents in supporting learning continuity at home. This research emphasizes the importance of an integrated support ecosystem to optimize students' functional independence post-school.